Revolutionary War diary
Printed version of Bickerstaff's Boston almanack for 1775, containing brief handwritten diary entries listing whaling vessel arrivals and departures, kept by an unknown individual.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Almanacs, American -- Massachusetts -- Boston; Whaling -- Massachusetts; Boston (Mass.) -- History -- Revolution, 1775-1783.; Massachusetts -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Personal narratives